Universal Strategy for Reversing Aging and Defects in Graphene Oxide for Highly Conductive Graphene Aerogels - Kumar, Prabhat; Šilhavík, Martin; Zafar, Zahid Ali; Červenka, Jiří (The journal of physical chemistry. C, Nanomaterials and interfaces, 2023)
The production of highly stable, defect-free, and electrically conducting 3D graphene structures from graphene oxide precursors is challenging. This is because graphene oxide is a metastable material whose structure and chemistry evolve due to aging. Aging changes the relative composition of oxygen functional groups attached to the graphene oxide and negatively impacts the fabrication and properties of reduced graphene oxide. Here, we report a universal strategy to reverse the aging of graphene oxide precursors using oxygen plasma treatment. This treatment decreases the size of graphene oxide flakes and restores negative zeta potential and suspension stability in water, enabling the fabrication of compact and mechanically stable graphene aerogels using hydrothermal synthesis. Moreover, we employ high-temperature annealing to remove oxygen-containing functionalities and repair the lattice defects in reduced graphene oxide. This method allows obtaining highly electrically conducting graphene aerogels with electrical conductivity of 390 S/m and low defect density. The role of carboxyl, hydroxyl, epoxide, and ketonic oxygen species is thoroughly investigated using X-ray photoelectron and Raman spectroscopies. Our study provides unique insight into the chemical transformations occurring during the aging and thermal reduction of graphene oxide from room temperature up to 2700 °C.